Greenland, Hisinger Glacier at Dicksons Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig. 198 - The head of Dickson Fiord from the southern side looking east. The front of Hisinger Glacier is in the foreground; the Veslekari is seen in the center of the view. Aug. 6, 1931. (XII). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp.134). New York: American Geographical Society.) The head of Dickson Fiord from the southern side looking east. The front of Hisinger Glacier is in the foreground, the Veslekari is seen in the center of the view. Aug. 6, 1931. See: Fiord Region of East Greenland, Fig. 198 Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society